Islāmic Approach to Social Justice: An Analytical Study - Nazir Zargar (al-Afkar, Journal For Islamic Studies, 2023)
Islām is the religion of peace and justice. The Islāmic Sharī‘ah is principally based upon the benefit of the beings. Hence it is against class conflict and establishes fraternity and brotherhood in the ranks of the Ummah.  As such, the Law of Islām holds that initially and essentially, all beneficial actions are legitimate, and all harmful ones are illegitimate. Justice is the fundamental principle existing in every commandment of the Sharī‘ah. That is why every rule of the Sharī‘ah bears witness to this generalisation when it considers human nature and its general weaknesses and basic needs. Justice is central to all the teachings and legal commandments of Islām. This paper explores the meaning of social justice. It analyses the fundamental ideals of Islām that can be considered to promote social justice, especially in societies governed by the legal system of Islām. It offers a conceptual framework primarily in light of the teachings of the Qur’ān. It also discusses the peculiar characteristics of the Sharī‘ah in light of the Islāmic Concept of the relationship between God, man, and the universe and the concept of divine justice manifest at all levels of the universe